THE IDEOLOGY OF JOKOWI AS INDONESIAN PRESIDENT IN CRITICAL DISCOURSE ANALYSIS STUDY - Elisabeth Septiani Munandar; Indah Arvianti; Ahmad Muhid (Jurnal CULTURE (Culture, Language, and Literature Review), 2021)
People as social human beings need a language for communication in daily activities. Communication can be found in many forms, one of them is speech. Thus, related to speech and the function of the speech to society the writer is interested in analysing the language, power and ideology in the speech of President Jokowi’s. This study uses critical discourse analysis theory, where it can be found that ideology can be revealed with the use of vocabulary, grammar and text structure of the speaker. The writer uses qualitative method by analysing Jokowi’s speech transcript. The writer also uses identity method by applying sociolinguistics method and pragmatic method. For presenting the data, the writer uses informal method. The writer found eight ideologies in analysing Jokowi’s speech such as the ideology of equality, the ideology in unity, the ideology to honour the law, the ideology of social justice, the ideology in prioritizing citizen, the ideology of national prosperity, the ideology of hard working, and the ideology in assertiveness. The result of this study shows a proof about the relationship between language, power, and ideology. As an Indonesian president, Jokowi has the power to choose the utterance in his speech. Through power over language, Jokowi can reveal the ideology that he holds so that the citizens can understand and follow his ideology.